153k views
17 votes
What is the recursive rule for the sequence?

What is the recursive rule for the sequence?-example-1
User Brindy
by
5.3k points

1 Answer

12 votes

Answer:

2nd option

Explanation:

the recursive rule is


a_(n) =
a_(n-1) + d ( d is the common difference )

use the explicit rule to find a₁ and d

a₁ = 48 - 11(1) = 48 - 11 = 37

a₂ = 48 - 11(2) = 48 - 22 = 26

then

d = a₂ - a₁ = 26 - 37 = - 11

recursive rule is then


a_(n) =
a_(n-1) - 11

a₁ = 37

User Pxeba
by
5.4k points